2012
DOI: 10.1177/145749691210100313
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Analysis of Postoperative Complications of Antebrachium Ten-Nailing in 35 Children

Abstract: Background: unstable antebrachium diaphyseal fractures in children are nowadays increasingly treated operatively by elastic intramedullary nailing.Aim: Aim of the study was to critically assess both radiological and functional outcome of antebrachium fractures treated by titanium elastic nail (ten) in a pediatric cohort.Material and Methods: this retrospective study investigated 75 consecutive children, who were treated for antebrachium shaft fractures at tampere university hospital during the time period from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Weinberg et al 14 reported one refracture (2.5%) without mentioning the treatment method. Salonen et al 18 describes three refractures of which one was treated with replacement of the nails and above elbow cast, one was treated conservatively but it remains unclear in which manner and the last was a patient with a bone fracture of which the plate osteosynthesis of the ulna had to be revised after a refracture as well as the intramedullary nail in the radius was replaced by plate osteosynthesis. Garg et al 15 treated their refracture, one of 21 (4.8%), with replacement of the intramedullary nail and above elbow plaster cast for 2–4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Weinberg et al 14 reported one refracture (2.5%) without mentioning the treatment method. Salonen et al 18 describes three refractures of which one was treated with replacement of the nails and above elbow cast, one was treated conservatively but it remains unclear in which manner and the last was a patient with a bone fracture of which the plate osteosynthesis of the ulna had to be revised after a refracture as well as the intramedullary nail in the radius was replaced by plate osteosynthesis. Garg et al 15 treated their refracture, one of 21 (4.8%), with replacement of the intramedullary nail and above elbow plaster cast for 2–4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Flexible intramedullary nailing is a preferred fixation method for pediatric forearm fractures. Most series showed good to excellent results using this method (13)(14)(15). The rate of complications associated with TENs has been reported to be 15-67% in the literature (16,17).…”
Section: Discussionmentioning
confidence: 92%
“…[1,13,21–23] A wide range of complication rates between 15% and even 67% for intramedullary fixation is reported in the literature. [15,16] Flynn and Waters [24] reported a rate of 14.6%, Smith et al reported a rate of 42%, [25] whereas Shah et al [26] reported no complications after intramedullary nailing and Antabak et al [27] a rate of 25% in 88 children. In the present study population with a large cohort of 202 fractures, we observed a low total complication rate of 8.9%, of which only 6.9% required a second operative intervention.…”
Section: Discussionmentioning
confidence: 99%
“…[1014] A wide range of complication rates have been reported in the literature. Salonen et al [15] reported in 2012 a complication rate of 67% in patients over 10 years and 33% in patients under 10 years. A complication rate of 15% was reported in a large cohort by Fernandez et al [16] in 2010.…”
Section: Introductionmentioning
confidence: 99%